Ecuador’s Ministry of Agriculture and Livestock (MAG) wins an award for the national digital soil fertility map that is being used to prevent land degradation. - Silva, Mayesse Aparecida da (2022)
The Alliance of Bioversity and CIAT helped Ecuador's Ministry of Agriculture and Livestock develop and implement nationwide digital maps of physicochemical soil properties and soil fertility. These maps are being used by the Ministry, local authorities, and others in five provinces for land use planning aimed at reducing land degradation. The Ministry won an award for producing the best thematic map in 2022 and continues to disseminate the maps to all provinces.